High-efficient and environmental-friendly PTFE@SiO2 core-shell additive with excellent AW/EP properties in PAO6. (June 2021) - Wang, Na; Wang, Honggang; Ren, Junfang; Gao, Gui; Zhao, Gengrui; Yang, Yawen; Wang, Jinqing
Abstract: Environmental-friendly polytetrafluoroethylene@silica (PTFE@SiO2 ) composite particles characterized by core-shell structure were synthesized. The tests demonstrated that the synthesized particles had good dispersibility and stability in poly-α-olefin 6 (PAO6) and its corrosion resistance was better than zinc dialkyl dithiophosphate (ZDDP). The extreme pressure (EP) and tribological tests evidenced that PTFE@SiO2 particles possessed superior EP and anti-wear (AW) properties, which could enhance the wear-resistance and load-bearing capacities of PAO6 in high efficiency, whereas the tribological performance was greatly affected by the load. Besides, EP tests for different kinds of base oils demonstrated that the addition of PTFE@SiO2 particles could significantly improve the bearing capacity of these base oils, and the corresponding performances were also better than ZDDP. Scanning electron microscope and X-ray photoelectron spectrum characterizations proved that there was an organic-inorganic co-extruded transfer film generated on the worn surface, and a possible lubrication mechanism on this basis was also put forward. Highlights: PTFE@SiO2 particles have good dispersibility and stability in PAO6 oil. PTFE@SiO2 particles have better corrosion resistance than ZDDP as oil additive. PTFE@SiO2 particles have superior extreme pressure and anti-wear properties. An organic-inorganic co-extruded transfer film is generated on the worn surface.